The Effect of Reading Habits at Home and the Availability of Reading Materials on the Reading Literacy Ability of Sixth-Grade Students at UPT SD Negeri 1 Kulo - Asnih; Muhammad Hanafi; Yusmah; Nuraini K; Aswadi; Jamaluddin Ahmad (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study investigated the influence of reading habits at home and the availability of reading materials on the reading literacy ability of sixth-grade students at UPT SD Negeri 1 Kulo. Employing a quantitative explanatory research design, the study utilized saturated sampling involving the entire population of 23 sixth-grade students. Data were collected using questionnaires to measure reading habits at home and the availability of reading materials, along with a standardized reading literacy test. Data were analyzed using descriptive statistics and multiple linear regression with SPSS software. The results revealed that: (1) reading habits at home had a positive and significant effect on reading literacy ability (t = 3.12, p = 0.005 < 0.05); (2) the availability of reading materials also exerted a positive and significant effect (t = 2.45, p = 0.021 < 0.05); and (3) both variables simultaneously had a significant influence (F = 18.76, p = 0.000 < 0.05). The coefficient of determination (R² = 0.652) indicated that 65.2% of the variance in students’ reading literacy ability could be explained by the two variables, while the remaining 34.8% was influenced by other factors. The findings underscore the critical role of home-based reading practices and resource availability in enhancing elementary students’ reading literacy. Collaboration among parents, teachers, and schools is essential to create a literacy-rich home environment that optimally supports students’ reading development.